Pendekatan Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Peserta Didik - Mufida, Fajriana; Mukmin, Bagus Amirul; Putra, Aji Setya Gaya (Cipta Media Harmoni, 2025)
This study is based on the fact that students at SDN Burengan 2 Kediri have not achieved the Learning Objective Achievement Criteria (KKTP) in learning economic activity material in Science, caused by the method used is still teacher-centered and the lack of active interaction of students, so that the understanding of the concepts taught is not optimal. The purpose of this study was to determine how the application of differentiated learning can improve the learning outcomes of fourth grade students in economic activity material at SDN Burengan 2 Kediri. This study is a qualitative PTK based on the I Kemmis and McTaggart model and is carried out in two cycles, with planning, action, observation, and reflection as steps. To collect data, observation, learning outcome tests, questionnaires, and documentation were used. To measure the increase in learning outcomes, descriptive quantitative and qualitative analysis were used. The results of this study indicate that differentiated learning is able to meet learning needs well.